2017
DOI: 10.4236/msa.2017.811058
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Sensors Based on Modification of Carbon Fiber Microelectrode by Nickel Phthalocyanine Polymer for 3-Methyl-4-Nitrophenol Analysis in Water

Abstract: Abstract3-methyl-4-nitrophenol (MNP) is the main by-product of the organophosphate insecticide fenitrothion (FT), used in locust control. MNP is highly toxic because it is an endocrine disruptor and then may cause adverse in the biological systems. Then, it is necessary to develop analytical methods for determination of this pollutant in the environment. In this sense, we reported herein the development of an electrochemical sensor for the detection of 3-methyl-4-nitrophenol (MNP), one of the metabolites of fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Figure 7 shows that the peak current varies linearly with the concentration of MNP in the range of 10 -100 μg/L with a regression equation of I_p (nA) = 2.68C (μg/L) + 358 and a limit of detection (3 S/m) of 1.1 μg/L. Although this value is very similar to the detection limit obtained in our previous work (previous LoD = 0.75 μg/L) [1] when detecting MNP in direct oxidation of the phenol group, analysis in indirect oxidation could be attractive to exploit because it is without risk of passivation. Thus, considering the proximity of the detection limit values, indirect MNP oxidation analysis could be an alternative to direct MNP oxidation detection without altering its sensitivity through any electrode passivation.…”
Section: Quantitative Analysis Of Mnpsupporting
confidence: 82%
See 2 more Smart Citations
“…Figure 7 shows that the peak current varies linearly with the concentration of MNP in the range of 10 -100 μg/L with a regression equation of I_p (nA) = 2.68C (μg/L) + 358 and a limit of detection (3 S/m) of 1.1 μg/L. Although this value is very similar to the detection limit obtained in our previous work (previous LoD = 0.75 μg/L) [1] when detecting MNP in direct oxidation of the phenol group, analysis in indirect oxidation could be attractive to exploit because it is without risk of passivation. Thus, considering the proximity of the detection limit values, indirect MNP oxidation analysis could be an alternative to direct MNP oxidation detection without altering its sensitivity through any electrode passivation.…”
Section: Quantitative Analysis Of Mnpsupporting
confidence: 82%
“…Organophosphorus (OPs) compounds are commonly used pesticides to control insects and improve crop yields. In Burkina Faso, fenitrothion (FT), an organophosphate insecticide, is widely used in cotton cultivation and during locust invasions [1] [2]. Like other organophosphates, FT acts by inhibiting acetylcholinesterase, which disrupts nerve impulse transmission [3] [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies were reported the use of Poly-NiTSPc film modified electrodes for different applications such as methanol electro-oxidation on a Pt/C catalyst [20], free sulfite electrooxidation [21], detection of 3-methylpara-nitrophenol (MNP) [22], Methyl-parathion (MPT) [23], 4-Nitrophenol (PNP) [24] and nitrite [25], determination of dopamine (DA) in the presence of ascorbic acid (AA) and uric acid (UA) [26], NO microsensor [27] and Microbial Fuel Cells [28]. Several studies were reported the use of Poly-NiTSPc film modified electrodes for different applications such as methanol electro-oxidation on a Pt/C catalyst [20], free sulfite electrooxidation [21], detection of 3-methylpara-nitrophenol (MNP) [22], Methyl-parathion (MPT) [23], 4-Nitrophenol (PNP) [24] and nitrite [25], determination of dopamine (DA) in the presence of ascorbic acid (AA) and uric acid (UA) [26], NO microsensor [27] and Microbial Fuel Cells [28].…”
Section: Introductionmentioning
confidence: 99%
“…The curve of the variation of the potential as a function of the pH is shown in (Figure 5C) from which the potential was shown to decrease linearly as the pH increases. The slope of the linear regression was estimated at 73 mV/pH indicating that there is a transfer of one electron per proton [46, [51][52][53]. Furthermore, the representation of the peak current as a function of the pH (Figure 5D) indicates a maximum current reached at pH = 8.…”
Section: Effect Of Phmentioning
confidence: 99%